Efek Mediasi Adaptive Selling Behavior pada Pengaruh Stres Kerja dan Pengalaman Kerja Terhadap Kinerja - Zulkifli; Christiana, Maria; Sulistiowati (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to examine the effect of Job Stress, Work Experience, Adaptive Selling Behavior on Salesperson Performance at Anzon Toyota West Kalimantan Branch, using Adaptive Selling Behavior data as a Mediating Variable. Data was collected through questionnaires distributed to salespeople at Anzon Toyota West Kalimantan, especially at the branches of Anzon Toyota Pontianak, Anzon Toyota Singkawang and Anzon Toyota Sintang. Data analysis was performed using Partial Least Squares (PLS). The results showed that Job Stress has a positive and significant effect on Adaptive Selling Behavior, with a path coefficient of 0.215 or p-value (0.006 <0.05). Work Experience has a positive and significant effect on Adaptive Selling Behavior, with a path coefficient of 0.625 or p-value (0.000 <0.05). Job Stress has a positive and significant effect on salesperson performance with a path coefficient of 0.354 or p-value (0.000> 0.05). Work Experience has a positive and insignificant effect on salesperson performance with a path coefficient of 0.041 or p-value (0.789 <0.05). Adaptive Selling Behavior has a positive and significant effect on salesperson performance with a path coefficient of 0.438 or p-value (0.001 <0.05). Job Stress affects performance through Adaptive Selling Behavior with a mediation path coefficient of 0.094 or p-value (0.020 < 0.05). Work Experience affects performance through Adaptive Selling Behavior with a mediation path coefficient of 0.274 and p-value (0.005 < 0.05). These findings conclude that Anzon Toyota needs to further improve the skill and competency development program of salespeople, especially on the implementation of adaptive selling behavior, more proactive management of work stress and balancing work experience with knowledge and skills of salespeople.